Комплексна оцінка токсичності водних зразків за допомогою рослинних і тваринних тест-організмів - Осмалений, М.С.; Головков, А.М.; Нанієва, А.В.; Верголяс, М.Р. (Фактори експериментальної еволюції організмів, 2015)
Aims. Developing effective methods for assessing the quality of natural waters by biological methods. Methods. In the study of the infl uence of toxic substances have used test organisms of plant and animal origin. Determined mitotic activity and frequency of micronuclei formation and double nuclei in cells proliferate roots and A. cepa, L. sativa, and analyzed ectodermal cells H. attenuata, exposed to the test solution conditions toxicological experiment. Results. The reaction of plants and animals on the negative impact of the compounds differed signifi cantly, indicating that their different sensitivities and necessitates sharing in complex biotests both plants and animals. It is shown that the animal organism differed greater sensitivity compared with plant, but plant bioassays observed more accurate reproducibility. Conclusions. The content and cytotoxicity of water samples using nucleolar biomarker in the cells of plants and animals. The method allows to identify the impact of toxicants in water content in the nuclei of cells. During the study, there was genotoxic action of organic and inorganic impurities aquatic environment of the test organism proved that the fabric of different organisms are sensitive and allows for assessment of toxicity, cytotoxicity and genotoxicity of water samples. Keywords: aquatic environment, test organism toxicity.